Transforming growth factor β latency: a mechanism of cytokine storage and signalling regulation in liver homeostasis and disease - Li, Yujia; Fan, Weiguo; Link, Frederik; Wang, Sai; Dooley, Steven (JHEP reports, 2022)
Transforming growth factor-β (TGF-β) is a potent effector in the liver, which is involved in a plethora of processes initiated upon liver injury. TGF-β affects parenchymal, non-parenchymal, and inflammatory cells in a highly context-dependent manner. Its bioavailability is critical for a fast response to various insults. In the liver - and probably in other organs - this is made possible by the deposition of a large portion of TGF-β in the extracellular matrix as an inactivated precursor form termed latent TGF-β (L-TGF-β). Several matrisomal proteins participate in matrix deposition, latent complex stabilisation, and activation of L-TGF-β. Extracellular matrix protein 1 (ECM1) was recently identified as a critical factor in maintaining the latency of deposited L-TGF-β in the healthy liver. Indeed, its depletion causes spontaneous TGF-β signalling activation with deleterious effects on liver architecture and function. This review article presents the current knowledge on intracellular L-TGF-β complex formation, secretion, matrix deposition, and activation and describes the proteins and processes involved. Further, we emphasise the therapeutic potential of toning down L-TGF-β activation in liver fibrosis and liver cancer.
Online verfügbar: 18. November 2021, Artikelversion: 10. Januar 2022
Im Titel ist beta als griechischer Buchstabe geschrieben
Gesehen am 07.05.2024